2020
DOI: 10.2105/ajph.2020.305605
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Tanning Trends Among US Adults, 2007–2018

Abstract: Objectives. To examine indoor tanning trends among US adults, and the relation to indoor tanning youth access legislation. Methods. This study analyzed the Health Information National Trends Survey (HINTS), a mailed survey, from the years 2007, 2011, 2013, 2014, 2017, and 2018 (combined n = 20 2019). Results. Indoor tanning prevalence decreased significantly over time among all US adults from 2007 (10%) to 2018 (4%; P < .001), among young adults aged 18 to 34 years (14% to 4%; P < .001), and among both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…This represents a statistically significant change (p < 0.0001) from the 2014′s estimate. The 2019s estimate (3%) is comparable to the United States’ 2018 indoor tanning prevalence estimate of 4%; to which the US has shown a 6% decrease from 11 years earlier ( Bowers et al, 2020 ). Taken together, these study findings show a similar 6% decline of tanning equipment use in North America over the last 13 years ( Fig.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This represents a statistically significant change (p < 0.0001) from the 2014′s estimate. The 2019s estimate (3%) is comparable to the United States’ 2018 indoor tanning prevalence estimate of 4%; to which the US has shown a 6% decrease from 11 years earlier ( Bowers et al, 2020 ). Taken together, these study findings show a similar 6% decline of tanning equipment use in North America over the last 13 years ( Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The current study found 11.8% E of tanning equipment users did not wear eye protection which is similar to a prevalence of 14.0% of users who did not wear eye protection in 2014. Other studies have reported a higher prevalence of tanning equipment users not wearing protective goggles ( Bowers et al, 2020 , Knight et al, 2002 , Szepietowski et al, 2002 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although we observed increased sunbed use in more recent birth cohorts compared to older ones, sunbeds and indoor tanning have become increasingly regulated by governments, including outright bans and restricted use by minors [ 36 , 37 ]. In the last two decades, sunbed use has trended downwards among adolescents and adults globally [ 36 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A promising decline in indoor tanning rates among US adults from 2007 to 2018 has followed the passage of legislation limiting youth access to indoor tanning in several states including Illinois 3 . Although SMM’s indoor tanning has been described in the literature, less is known about the prevalence and motives for outdoor tanning.…”
Section: Survey Questionsa Test–retest Reliability (Alpha)b Occasional Tanning Two To 10 Times In 3 Monthsc (N = 88) Frequent Tanning >mentioning
confidence: 99%